2021
DOI: 10.1037/mot0000211
|View full text |Cite
|
Sign up to set email alerts
|

Punishment-modulated attentional capture is context specific.

Abstract: Attention prioritizes stimuli previously associated with punishment. Despite the importance of this process for survival and adaptation, the potential generalization of punishment-related attentional biases has been largely ignored in the literature. This study aimed to determine whether stimulus-punishment associations learned in a specific context bias attention in another context (in which the stimulus was never paired with punishment). We examined this issue using an antisaccade task in which participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
2
12
1
Order By: Relevance
“…In contrast to the present results, both reward-and punishment-based learning, which directly associate stimulus features with some outcome, have context-dependent effects on attentional priority (Anderson, 2015;Anderson & Kim, 2018;Grégoire et al, 2020). This is suggestive of a distinction between associative learning and statistical learning in the way they treat context.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the present results, both reward-and punishment-based learning, which directly associate stimulus features with some outcome, have context-dependent effects on attentional priority (Anderson, 2015;Anderson & Kim, 2018;Grégoire et al, 2020). This is suggestive of a distinction between associative learning and statistical learning in the way they treat context.…”
Section: Discussioncontrasting
confidence: 99%
“…It is assumed that the three components of attentional selection (top-down, bottom-up, and selection history) are combined in an integrated priority map, where the input with the highest priority is selected in a winner-takes-all fashion (Theeuwes, 2018). Selection history effects are studied in paradigms such as contextual cueing (Chun & Jiang, 1998;Goujon et al, 2015), reward or punishment learning (Anderson et al, 2011;Della Libera & Chelazzi, 2009;Grégoire et al, 2020), and as of recently statistical learning of distractor suppression (e.g., Ferrante et al, 2018;Wang & Theeuwes, 2018b). Of interest to the current study, contextual cueing, reward learning, and punishment learning have been shown to involve contextdependent learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previous studies demonstrating that spatial attentional biases arising from reward learning are contingent upon awareness of the reward contingencies (Mine et al, 2021; Sisk et al, 2020; see also Anderson & Kim, 2018a, 2018b; Liao et al, 2021), which contrasts with the influence of reward learning and aversive conditioning on feature-based attention that can be implicit (Grégoire & Anderson, 2019; Grégoire et al, 2021, 2020; Hopkins et al, 2016; Leganes-Fonteneau et al, 2018, 2019), suggesting a fundamental difference between how selection history shapes feature-based and space-based attentional biases. Like feature-based attentional biases arising from both reward learning and aversive conditioning, however, Pavlovian learning is implicated, which may reflect a broad principle in the selection history-dependent control of attention.…”
Section: Discussionsupporting
confidence: 92%
“…In the case of value-driven attention, if a stimulus is associated with reward in one context but not in another, attentional capture by that stimulus will be specific to when it appears in the context in which it was rewarded (Anderson, 2015a, 2015b; see also Anderson & Kim, 2018a, 2018b). Likewise, attentional capture by aversively conditioned stimuli is context-specific (Grégoire et al, in press). At the same time, if context is not diagnostic of whether a particular stimulus predicts a reward during learning, there is a tendency to generalize such learning to attention allocation in a novel context (Anderson et al, 2012).…”
Section: A Revised Model Of Adaptive Attentional Controlmentioning
confidence: 99%